2015
DOI: 10.1037/gpr0000029
|View full text |Cite
|
Sign up to set email alerts
|

Action Change Theory: A Reinforcement Learning Perspective on Behavior Change

Abstract: Traditional theories of behavior change rely mostly on influencing higher-order mental processes as a route to altering deliberate responses, whereas more recent theorizing postulates that interventions can also rely on using contextual cues influencing lower-order processes as a route to changing spontaneous responses. We propose an alternative mechanistic account based on reinforcement learning theory, which utilizes different action control systems in the brain. Therefore, this account works at a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 241 publications
(294 reference statements)
2
44
0
2
Order By: Relevance
“…It has been shown that interventions connected to theories are more effective relative to those which are not (e.g., Webb, Joseph, Yardley, and Michie, ; Painter, Borba, Hynes, Mays, & Glanz, ). We also found that in each study, the applied interventions were connected to some choice architecture theories or frameworks (e.g., Smith, Goldstein, & Johnson, ; Vlaev & Dolan, ; Dolan et al, ). However, our findings also point to an important characteristic of the literature: the main motivation of the studies was overwhelmingly the assessment of the intervention effectiveness in a given setting, and in only fewer than the half of the studies was the emphasis on the development of theories and the deeper understanding of the causal processes.…”
Section: Discussionmentioning
confidence: 85%
“…It has been shown that interventions connected to theories are more effective relative to those which are not (e.g., Webb, Joseph, Yardley, and Michie, ; Painter, Borba, Hynes, Mays, & Glanz, ). We also found that in each study, the applied interventions were connected to some choice architecture theories or frameworks (e.g., Smith, Goldstein, & Johnson, ; Vlaev & Dolan, ; Dolan et al, ). However, our findings also point to an important characteristic of the literature: the main motivation of the studies was overwhelmingly the assessment of the intervention effectiveness in a given setting, and in only fewer than the half of the studies was the emphasis on the development of theories and the deeper understanding of the causal processes.…”
Section: Discussionmentioning
confidence: 85%
“…Research has shown that there are three core brain systems for behavioral decision making, which generate specific psychological processes (thoughts, drives and emotions, and mental and motor habits) that independently cause behavior change (for a description of those brain structures and review of the evidence, see Vlaev and Dolan ). Figure presents the self‐regulatory processes involved in behavioral change.…”
Section: Understanding Behaviormentioning
confidence: 99%
“…Those taxonomies of BCTs, derived from systematic reviews of the available evidence, differentially engage the behavioral control systems (regulatory processes). Vlaev and Dolan () describe how traditional BCTs (e.g., Abraham and Michie ) target the goal‐directed system and are supposed to persuade or train recipients to adopt a specific behavior. Such techniques might include “provide information about behavior‐health link,” “provide information on consequences,” “plan social support,” “prevent relapse,” “prompt intention formation,” “prompt specific goal setting,” or “prompt review of behavioral goals.” Economists and psychologists have also convincingly demonstrated that people respond to “incentives,” which usually activate reflective thinking and motivation by changing the evaluation of the available courses of action (e.g., people rationally respond to changes in prices and costs).…”
Section: Understanding Behaviormentioning
confidence: 99%
“…Planning and development processes depend on social learning (see Friedmann and Abonyi 1976;Rydin 2010;Scholz, Dewulf, and Pahl-Wostl 2014;Vlaev and Dolan 2015;Young 2009). Social learning is the process of developing knowledge (including skills and experiences) through human interaction.…”
Section: Introductionmentioning
confidence: 99%